Association of the p22phox polymorphism C242T with the risk of late-onset Alzheimer's disease in a northern Han Chinese population. (2nd July 2016) - Fu, Qingxi; Qi, Faying; Tian, Fengyun; Ma, Guozhao; Che, Fengyuan; Du, Yifeng; Gao, Naiyong
Abstract : The C242T polymorphism of the CYBA gene that encodes p22phox, a component of nicotinamide adenine dinucleotide phosphate oxidase, has been found to modulate reactive oxygen species (ROS) production. Oxidative stress is thought to play a pivotal role in the pathophysiology of Alzheimer's disease (AD), which is manifested as increased availability of ROS because of an imbalanced redox state. Therefore, the aim of this study was to investigate potential associations of the p22phox C242T polymorphism with the risk of late-onset AD (LOAD) in a northern Han Chinese population. Patients with LOAD ( n = 276) and 320 control subjects were recruited for the study. Polymerase chain reaction-restriction fragment length polymorphism was used to detect the genotypes. No significant differences were found between LOAD and p22phox C242T polymorphism, but a significant association was obtained in the genotype and allele distributions of p22phox C242T between LOAD patients and controls in apolipoprotein E (ApoE) ϵ4 carriers. These results suggested that p22phox C242T polymorphism has a possible role in changing the genetic susceptibility to LOAD in ApoE ϵ4 carriers of this northern Han Chinese population.